The miniaturist - Burton, Jessie, 1982- (New York : Ecco, an imprint of HarperCollinsPublishers, 2014)
Engaging the services of a miniaturist to furnish a cabinet-sized replica of her new home, 18-year-old Nella Oortman, the wife of an illustrious merchant trader, soon discovers that the artist's tiny creations mirror their real-life counterparts in eerie and unexpected ways.
Maps on lining papers.
Includes glossary of Dutch terms.
Keywords: Young women -- Fiction; Miniature painters -- Fiction; Merchants -- Netherlands -- Amsterdam -- Fiction; Amsterdam (Netherlands) -- Social life and customs -- 17th century -- Fiction; Historical fiction